Twenty Years of Socio-Economic Research on Organic Agriculture Across the World: Looking at the Past to Be Ready for the Future - Leonardo Cei; Gianluca Stefani; Luca Rossetto (Agriculture)
The world organic sector has evolved in a rapid way over the last few decades, driven by consumer interest, producer and retailer strategies, as well as by the evolving normative context. This growth has stimulated an increase in academic research, particularly in socio-economic research. The present work aims to understand the evolution of organic socio-economic research in terms of the research themes covered within this field, their relative importance, and how this importance has changed over time. The implementation of a structural topic model on scientific abstracts from the last 20 years allowed us to identify three broad areas of interest for organic socio-economic researchers: consumers, production, and society. The relevance of these strands varies in different areas of the world, mostly aligning with the prominent aspects of local organic sectors. This signals a good integration of organic socio-economic research within local contexts, with the possible development of place-based skills to be exploited within the global debate on organic agriculture. Overall, a reasonably strong imbalance emerges, with consumer-focused studies being more prominent than production-focused ones, especially those investigating producers’ economic results. The latter seems to call for renewed attention on and analysis of the organic sector, assisted by robust evidence on both ends of the organic supply chain.